2015
DOI: 10.1158/0008-5472.can-14-1903
|View full text |Cite
|
Sign up to set email alerts
|

Snail1-Expressing Fibroblasts in the Tumor Microenvironment Display Mechanical Properties That Support Metastasis

Abstract: Crosstalk between tumor and stromal cells in the tumor microenvironment alter its properties in ways that facilitate the invasive behavior of tumor cells. Here, we demonstrate that cancer-associated fibroblasts (CAF) increase the stiffness of the extracellular matrix (ECM) and promote anisotropic fiber orientation, two mechanical signals generated through a Snail1/RhoA/aSMAdependent mechanism that sustains oriented tumor cell migration and invasiveness. Snail1-depleted CAF failed to acquire myofibroblastic tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
137
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 108 publications
(145 citation statements)
references
References 43 publications
7
137
1
Order By: Relevance
“…Next, we determined and contrasted the nature of the ECM produced by CAFs and CAFs lacking SNAIL1. As reported by Stanisavljevic et al (2015) , we also observed that matrix produced by WT CAFs, as assessed by fibronectin fiber organization (Fig. 7C) and second harmonic generation (SHG) analysis of collagen fibers (Fig.…”
Section: Ecm-stiffness-induced Rock Stabilizes and Activates Snail1 Tsupporting
confidence: 84%
See 4 more Smart Citations
“…Next, we determined and contrasted the nature of the ECM produced by CAFs and CAFs lacking SNAIL1. As reported by Stanisavljevic et al (2015) , we also observed that matrix produced by WT CAFs, as assessed by fibronectin fiber organization (Fig. 7C) and second harmonic generation (SHG) analysis of collagen fibers (Fig.…”
Section: Ecm-stiffness-induced Rock Stabilizes and Activates Snail1 Tsupporting
confidence: 84%
“…In response to ECM stiffness, CAFs increase matrix production and remodeling in a SNAIL1-dependent manner Recently, the action of SNAIL1 in CAFs has been shown to control the production of ECM and orientation of fibronectin fibers (Stanisavljevic et al, 2015). In contrast to breast tumor CAFs, normal breast fibroblasts did not express SNAIL1 protein, although they did express other EMT factors (SNAIL2, TWIST1 and ZEB1; Fig.…”
Section: Ecm-stiffness-induced Rock Stabilizes and Activates Snail1 Tmentioning
confidence: 94%
See 3 more Smart Citations